Simultaneous Determination of Magnesium (Mg2+) and Ammonium (NH4+) by Flow Injection Analysis - Kholifa, Mulik; Mulyono, Tri; Muflihah, Yeni Maulidah (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2018)
An automatic method for the simultaneous determination of magnesium and ammoniun by flow injection analysis is described. This analysis used two detectors, potentiometry and spectrophotometry, for the determination of magnesium and ammonium simultaneously. Potentiometric detectors are used to detect ammonium ions, whereas spectrophotometer detectors are used to detect the presence of magnesium ions. The performance of the FIA system includes linear range linearity, limit of detection, sensitivity, reproducibility and recovery test. Spectrophotometry FIA showed good performance with several criteria of linearity with regression value of 0.9918, the detection limit of 0.06 ppm, a sensitivity of 0.0115, repeatability of less than 2% and the percent recovery of 91,6%. While potentiometric FIA showed th performance with several criteria of linearity with regression value of 0.9896, the detection limit of 0.17 ppm, a sensitivity of 40.747 mV per decade of concentration, repeatability of less than 2% and the percent recovery of 89,7%. Keywords: Flow Injection Analysis, spectrophotometry, potensiometry, simultaneous